Manager : a simulation - Smith, Jerald R.; Golden, Peggy (Boston [Mass.] : Houghton Mifflin, 1997)
This book is about: History of the Industry and the Firm; The environment and process; Decision incidents; ...
Keywords: Management; Decision making; Management games; Management -- Simulation methods; Decision making -- Simulation methods